Application of Mutation Techniques in Sorghum Breeding for Improved Drought Tolerance - S Human; Sihono Sihono; Parno Parno (Atom Indonesia, 2006)
Sorghum is not native to Indonesia and has not yet as popular as other cereal crops. This crop has a big potential to be grown and cultivated owing to its wide adaptability and high productivity. Genetic variability of this crop is still low, thus, plant breeding program is required to support sorghum development in the country. The objective is to develop superior genotypes to improve sorghum production and quality, as food, animal feed or for industry. Research on sorghum improvement through induced mutations has been conducted at the Center for the Application of Isotope and Radiation Technology, National Nuclear Energy Agency (BATAN). Durra variety was used as parental material in the breeding program. Induced mutation was made by Gamma irradiation on seed treatments. The optimal radiation dose was to be around 300-500 Gy. Through selection processes and direct screening for drought tolerance, a number of ten putative mutant lines were obtained. In dry season, the mutant lines B-68, B-72, B-95 and B-100 produced grain yield of 4.55, 4.50, 4.20 and 4.62 t/ha, respectively. These yields were significantly higher than the original parent Durra (3.50 t/ha) and the control check varieties UPCA (2.68 t/ha) and Higari (3.75 t/ha). These promising mutant lines might be of useful for further sorghum research and development in Indonesia